Beyond Protest Voting: Membaca Pesan Tersembunyi di Balik Suara Tidak Sah - Prasetyo, Wegik (Political Science Program, Universitas Negeri Semarang, 2017)
This article related to the use of signs and symbols as a protest vote beyond the invalid votes of the presidential election 2014 in Daerah Istimewa Yogyakarta (DIY). This paper will interpret the hidden messages conveyed by voters through a ballot. This article contributes to solve two problems at once, the conceptual and practical. Conceptually, there is a gap in the study of protest voting. Protest voting describes that voting as not only used to support candidates or parties but can be used as a form of protest. However, in this paper the protest was not conveyed through voting but using signs, symbols, or messages in ballot. Practically, there are problems in the electoral system on viewing people votes. The current electoral system generalizes the approach on viewing invalid votes. Whereas, there some hidden messages of people votes and the essence of the election itself beyond the invalid ballot papers. This paper shows that these messages can not be accommodated by the current electoral system. Those include an indication of post-election money politics, expressions of blissful voters delivered on the ballot, the expletives and insults expressed by voters, a rejection of the candidates, and also a rejection for the current electoral system.